2012
DOI: 10.4261/1305-3825.dir.6070-12.1
|View full text |Cite
|
Sign up to set email alerts
|

The value of diffusion weighted MR imaging and apparent diffusion coefficient quantification in the diagnosis of perforated and non-perforated appendicitis

Abstract: ORIGINAL ARTICLE PURPOSE We aimed to evaluate the effectiveness of diffusion-weighted magnetic resonance imaging (DW-MRI) and apparent diffusion coefficient (ADC) values in the diagnosis of acute appendicitis and differentiation of perforated and nonperforated appendicitis cases, with histopathologic correlation. MATERIALS AND METHODSSixty consecutive patients (34 males, 26 females; mean age, 35.6±15.5 years; range, 17-83 years) with a presumptive diagnosis of acute appendicitis were included in this prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 13 publications
0
24
1
Order By: Relevance
“…Research is increasingly focused on the use of diffusionweighted sequences [39,40]. Leeuwenburgh et al discovered limited diffusion in the appendiceal wall as a reliable indicator of acute inflammation [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is increasingly focused on the use of diffusionweighted sequences [39,40]. Leeuwenburgh et al discovered limited diffusion in the appendiceal wall as a reliable indicator of acute inflammation [39].…”
Section: Resultsmentioning
confidence: 99%
“…Leeuwenburgh et al discovered limited diffusion in the appendiceal wall as a reliable indicator of acute inflammation [39]. Avcu et al also examined whether the ADC value plays a role in the differentiation between perforated and non-perforated appendicitis [40]. 60 adults with suspected appendicitis were included in this prospective study.…”
Section: Resultsmentioning
confidence: 99%
“…When transabdominal ultrasound was not groundbreaking, gynecologic examination should be performed principally in women to exclude differential diagnosis such as adnexitis or tubo-ovarian abscess. Furthermore, abdominal magnetic resonance imaging (MRI) without contrast administration is the method of first choice in women in childbearing age and pregnant women (hence, we excluded pregnant women from our study) with persistent suspicion of AA [25]. Additionally, MRI should be performed in young men with suspected AA.…”
Section: Discussionmentioning
confidence: 99%
“…Although magnetic resonance imaging (MRI) is not often used to diagnose AA, several studies have reported the benefits of utilizing MRI techniques in an emergency setting (19,20). Diffusion-weighted magnetic resonance imaging (DWI) of the abdomen and pelvis has been increasingly used since the 1990s, with the introduction of stronger diffusion gradients, faster imaging sequences and improvements in MRI hardware.…”
Section: Objectivesmentioning
confidence: 99%